(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2009)
Ambient (outdoor) air pollution is now recognized as an important problem, both nationally and worldwide. Our scientific understanding of the spectrum of health effects of air pollution has increased, and numerous studies are discovering important health effects from air pollution at levels once considered safe. Elderly, children and infants are among the most susceptible to many of the air pollutants. In addition to associations between air pollution and respiratory symptoms, asthma exacerbations, and asthma hospitalizations, recent studies have found links between air pollution and preterm birth, infant mortality, deficits in lung growth, and possibly, development of asthma. This paper summarizes the recent literature linking ambient air pollution to adverse health outcomes in population and includes a perspective on the current regulatory process. The review provides advice to pediatricians on how to integrate issues regarding air quality and health into patient education and patients’ environmental health advocacy and concludes with recommendations to the government on promotion of effective air-pollution policies to ensure protection of our health. DOI: 10.3329/bjpp.v22i1.3566 Bangladesh J Physiol Pharmacol 2006; 22(1/2) : 25-28